The housing wealth effect: Quasi-experimental evidence - Dany Kessel; Björn Tyrefors; Roine Vestman (Research Institute of Industrial Economics (IFN), 2019)
We exploit a quasi-experiment to provide new evidence on the magnitude of the housing wealth effect. We estimate an immediate shock of approximately -15% to house prices close to one of Stockholm's airports after its operations were unexpectedly continued as a result of political bargaining. This source of price variation is ideal to identify housing wealth effects since it is local and unrelated to variation in macroeconomic conditions. Using a household data set with granular geographic information on location of primary residence, we find an elasticity of 0.45 among purchasers of new cars. Converting our estimate to an aggregate MPC on cars, it is however only 0.13 cents per dollar. The MPC is entirely concentrated to homeowners with a combined loan-to-value ratio between 0.6 and 0.8 which, on the one hand, confirms the key role of household balance sheets but on the other hand refutes a monotone relationship between response and household leverage
Keywords: D12; E21; E32; E44; E60; 330; House prices; Housing wealth; Consumption; House price elasticity; Marginal propensity to consume; Collateral effect